2008
DOI: 10.1177/1933719108317584
|View full text |Cite
|
Sign up to set email alerts
|

Expression of C-kit and Platelet-Derived Growth Factor Receptors in Ovarian Granulosa Cell Tumors

Abstract: The data demonstrated significant expression of PDGFR targets of imatinib mesylate in GCTs, whereas normal ovarian tissues had a complete absence of staining.This expression profile provides the rationale to investigate the role of imatinib mesylate in PDGFR-positive GCTs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…In ovarian carcinoma, some studies have examined the biological role of PDGFRa and its efficacy as a therapeutic target. Stimulation of PDGFRa with its ligand, such as PDGF-AA, increases cell proliferation and activation of AKT and MAPK signaling, and neutralizing PDGFRa inhibited these signaling effects [17]. PDGFRA is verified as the direct target gene of miR-140-5p in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…In ovarian carcinoma, some studies have examined the biological role of PDGFRa and its efficacy as a therapeutic target. Stimulation of PDGFRa with its ligand, such as PDGF-AA, increases cell proliferation and activation of AKT and MAPK signaling, and neutralizing PDGFRa inhibited these signaling effects [17]. PDGFRA is verified as the direct target gene of miR-140-5p in ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 92%
“…Granulosa cell tumors (GCTs) are generally considered indolent tumors, but are associated with late recurrences, at which time the survival rate is significantly shortened (29). Previous studies have demonstrated the expression of PDGF receptors in both adult and juvenile forms of GCTs (30, 31), but the function or expression of PDGFA in JGCTs has not been reported. This tumor type is rare, and though our samples size is small, the majority of tumor samples used in the present study exhibited expression of PDGFA , PDGFRA and PDGFRB, suggesting that autocrine PDGF receptor stimulation could contribute to the tumor growth.…”
Section: Discussionmentioning
confidence: 94%
“…GCT also express a panel of molecular targets, like EGFR, c‐kit, PDGFRa‐b, c‐abl, m‐TOR and VEGF, but not others like Her‐2/neu. Anti‐EGFR, m‐TOR inhibitors and anti‐VEGF have been proposed as targeted therapies in GCT, as drugs acting against tyrosine kinase (PDGFR, c‐kit, c‐abl), with a reported response rate of 38% for bevacizumab 5–10 . Imatinib mesylate is a molecule inhibiting the tyrosine kinase c‐abl, c‐kit, PDGFR‐a, PDGFR‐b, leading cells to pro‐apoptotic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Imatinib mesylate is a molecule inhibiting the tyrosine kinase c‐abl, c‐kit, PDGFR‐a, PDGFR‐b, leading cells to pro‐apoptotic changes. It has first been used to treat Ph‐positive chronic myeloid leukemia (c‐abl), and also demonstrates to be active against gastrointestinal stromal tumor (GIST) (c‐kit) 5 . The in vivo use of imatinib in GCT was first reported by Jakob et al 11 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation